1987
DOI: 10.1111/j.1399-0004.1987.tb03335.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverted tandem duplication generates a duplication deficiency of chromosome 8p

Abstract: An adult female with severe mental retardation and dysmorphic features is described. A de novo chromosomal aberration involving 8p was found. The karyotype was 46, XX, inv dup (8) (pl2→p23.1). Dosage studies with the DNA probe D8S7, which is located at 8p23→8pter, showed that the patient was monosomic for this marker. Thus the de novo rearrangement generated a duplication‐deficiency chromosome. The possible mechanisms of formation of this abnormal chromosome are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…This is a recurrent rearrangement (about 1:20,000 newborns) reported in the literature since 1976 (1) associated with severe mental retardation, corpus callosum agenesis, important scoliosis in adulthood. The presence of an inverted duplication ("mirror duplication" (2)) had been hypothesized based on the banding pattern, whereas the demonstration that a concurrent deletion was also present in all inv dup(8p) cases had to wait for the availability of molecular techniques (3,4). Further molecular studies (5,6) on several cases demonstrated that the rearrangement had always the same breakpoints, with a single copy region of about 4-5 Mb interposed between the deletion and the duplication region.…”
Section: History Of a Recurrent Rearrangementmentioning
confidence: 99%
“…This is a recurrent rearrangement (about 1:20,000 newborns) reported in the literature since 1976 (1) associated with severe mental retardation, corpus callosum agenesis, important scoliosis in adulthood. The presence of an inverted duplication ("mirror duplication" (2)) had been hypothesized based on the banding pattern, whereas the demonstration that a concurrent deletion was also present in all inv dup(8p) cases had to wait for the availability of molecular techniques (3,4). Further molecular studies (5,6) on several cases demonstrated that the rearrangement had always the same breakpoints, with a single copy region of about 4-5 Mb interposed between the deletion and the duplication region.…”
Section: History Of a Recurrent Rearrangementmentioning
confidence: 99%
“…Since then, the application of molecular cytogenetic methods such as fluorescence in situ hybridisation (FISH) and array comparative genomic hybridisation (array CGH) has allowed for a significantly higher level of resolution for detecting and characterising chromosome abnormalities. As a result, the mechanisms responsible for this class of cytogenetic rearrangements have been better elucidated, and inverted duplication with concomitant terminal deletion has since been identified for a number of other chromosomes including 1p2 3 and 1q,4 2p,5 2q,6 3p,7 8 4p,9 10 11 and 4q,12 5p,13 14 7q,15 16 8p,17 18 19 20 9p21 and 9q,22 10p15 and 10q,15 11p,23 14q,8 24 25 15q,26 17p,27 18q,28 21q29 and Xp30 31 and in a variety of ring chromosomes 25 32…”
mentioning
confidence: 99%
“…Although the Utype exchange (mechanism 3) is the most frequent inv dup del mechanism in all other chromosome arms [Rowe et al, 2009], the majority of reported inv dup del(8p) can be explained by the mechanisms 1 or 2 mentioned above ( fig. 4 ; table 3 ) [Weleber et al, 1976;Dill et al, 1987;Minelli et al, 1993;Barber et al, 1994;de Die-Smulders et al, 1995;Guo et al, 1995;Floridia et al, 1996;Macmillin et al, 2000;Giglio et al, 2001;Pabst et al, 2003;Felbor et al, 2004;Shimokawa et al, 2004Shimokawa et al, , 2005Cooke et al, 2008;Zuffardi et al, 2009] with few exceptions [Buysse et al, 2009;Rowe et al, 2009]. In this study, the formation of the inv dup del(8p) appears to be caused by mechanism 2 in patient 2, and by mechanism 3 in patient 3 ( fig.…”
Section: Discussionmentioning
confidence: 76%